Web-Based Restaurant Management Information System at Adamsafee Bakery, Resto, and Cafe (ABRC) - Kharis Ferdiansyah; Supriyono Supriyono; Diana Laily Fithri (International Journal of Management Science and Information Technology, 2026)
Restaurants require integrated information management to connect ordering, payment, kitchen operations, sales transactions, and raw material management. At Adamsafee Bakery, Resto, and Cafe (ABRC), these activities required more structured information management to support restaurant operations and raw material handling. This study aims to develop a Web-Based Restaurant Management Information System at ABRC that integrates restaurant operational processes and applies the First in First Out (FIFO) method to raw material management. The study employed the System Development Life Cycle (SDLC) with the Waterfall model. Data were collected through observation, interviews, and literature study, while system design used Unified Modeling Language (UML). The implemented system supports ordering, payment, cashier order management, kitchen order management, raw material purchasing, material usage, and an owner dashboard. FIFO uses inventory receipt dates to determine the priority sequence of material usage, with recipe data providing the required material quantities for ordered menu items. Black-box Testing was conducted to examine the implemented system functions and FIFO mechanism based on specified testing scenarios. The results indicate that the tested functions operated according to their expected outputs, including the FIFO mechanism that prioritizes materials according to their receipt-date sequence. The study concludes that the implemented system integrates restaurant operational processes with raw material management and provides functional support for FIFO-based material usage. Quantitative impacts on operational efficiency, inventory accuracy, costs, material waste, and overall performance were not measured and therefore require further evaluation.